UPAYA MASYARAKAT DESA BANDAR BARU DALAM MENGUBAH STIGMA NEGATIF DESA NARKOBA MENJADI DESA SEJAHTERA DI DESA BANDAR BARU, KECAMATAN SIBOLANGIT, KABUPATEN DELI SERDANG - Mhd Ardiansyah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Drug abuse is a serious and very complex problem. Bandar Baru Village was formerly known as a stopover place for using the services of commercial sex workers (PSK). However, over time Bandar Baru Village turned into a place for drug trafficking. This makes many people fall into drug abuse. Bandar Baru Village is now known as a drug village because of the many acts of abuse among the people of Bandar Baru Village. With all the problems there are several efforts that have been made by the people of Bandar Baru Village to change the negative stigma that exists in this village, because this study aims to describe the efforts of the Bandar Baru village community in changing the negative stigma of a drug village into a prosperous village. The informants in this study were two addicts, the head of the youth organization, the head of the PKK, and two people from the new city community. Data collection techniques were carried out by literature study, observation, interviews and documentation. The data that has been collected will then be analyzed descriptively qualitatively and produce conclusions. The results of this study indicate that there are community empowerment efforts (promotive, preventive, curative, social action), rehabilitative and repressive carried out by the Bnadar Baru village community to change the stigma of Bandar Baru village from a drug village to a prosperous village.